Implication of liability transfer towards architect in the issuance of certificate of completion and compliance (CCC) in building industry - Norshahida Azili, 1985-, author 620753; Rosli Mohamad Zin, supervisor 282035; Samsiah Abdullah, supervisor 265957; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam 619085 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Kejuruteraan (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2019